Structural Determinants of Capital and Corporate Bonds and Their Implications on Yield to Maturity (YTM) and Economic Growth - Muhammad Mardiputra, Ilham; Syaiful, Syaiful; Halilintar, Muhamad (Dinasti Publisher, 2024)
This research is to now the determinant of DER and the implication toward YTM and Economic growth in Banking Sector on The Indonesian Stock Exchange. The research sample is 22 Bond Series which are banking companies listed on the Indonesia Stock Exchange for the 2019-2023 period. Methods of data analysis using panel data regression method. The empirical results of the first model show that Profitability (ROA), Firm Size (SIZE), and Interest Rate (IR) have a positive effect on Capital Structure (DER), while the Exchange Rate (FOREX) has a negative effect. Liquidity (CR) has no effect on DER. All independent variables consisting of; ROA, CR, SIZE, FOREX and IR together significantly influence DER. The goodness-of-fit test as measured by the termination coefficient (R2) shows a coefficient of 0.937202, meaning that the variation in the ups and downs of the DER can be explained by ROA, CR, SIZE, FOREX, and IR of 93.72 percent, while the rest, namely 6.28 percent can be explained by other variables not examined in this research model. For the adjusted coefficient of determination (R2 adjusted) the coefficient is 0.9217. The second model shows that the DER and IR variables have a negative effect on Yield to Maturity (YTM), while the SIZE and FOREX variables have a positive effect. ROA and CR variables have no effect on YTM. All variables DER, ROA, CR, SIZE, IR and FOREX together affect YTM. For the goodness-of-fit test as measured by the termination coefficient (R2) shows a coefficient of 0.6750, which means that the variation in changes in the rise and fall of YTM can be explained by; DER, ROA, CR, SIZE, IR, and FOREX are 63.30 percent, while the remaining 36.70 percent can be explained by other variables outside this research model.